The apothecary diaries. 9 - Hyūga, Natsu (Apothecary diaries (light novel), 2026)
"Maomao has effectively become Jinshi's personal physician, but she's just a simple apothecary. If she's going to give him proper medical treatment, she'll need more than her meager surgical skills. When she turns to her father for help, he says he'll only teach her if she can pass a test he sets for her. Even if she succeeds at his mysterious request, however, the truth behind the practice of surgery at court may be more than she cares to know. And only once she has the knowledge she needs will she be able to accompany Jinshi on what could be his most dangerous journey yet." --